SYNERGETIC APPROACH AS THE MAIN INNOVATION IN TE RUSSIAN ECONOMY MANAGEMENT - E. I. Galeyeva (Russian Journal of Economics and Law)
At present the Russian economy is transforming into the new management system, which is to provide the growth of production efficiency and social progress. This transition is connected with the implementation of the two constituents of synergetic mechanism of social-economic systems - the organizational and self-organizational ones. However, in the modern policy of the Russian reformism we can observe the definite distortion towards the organizational constituent to the prejudice of the self-organizational one, which gives rise to a lot of inadequate projects and solutions taken by the state government. The synergetic approach suggested in the article allows to balance the mechanism of Russian economy management and lead it to the new stage of development.